Inquiry-Flipped Classroom E-Worksheet to Train Critical Thinking Skills on Chemical Equilibrium Learning - Rahmadani, Reza Suci; Lutfi, Achmad (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This study aims to obtain a feasible e-worksheet to train students' critical thinking skills. This type of research includes research and development. The development model used refers to the 4-D model but is only limited to the define, design, and develop stages. The pilot test was conducted in one randomly selected class. The feasibility of the developed e-worksheet is guided by validity, practicality, and effectiveness. Validation was conducted by expert validators with scores determined based on mode values. The validation results obtained a score of 5 with a very valid category on the three e-worksheets. Practicality analysis results are seen from the results of the learner response questionnaire and learner activity observations. The percentage of practicality based on the students' response questionnaire was obtained at 98.08% with a very practical category. As for the results of the observation of students' activities, relevant activities were obtained at meeting 1 of 94.23%, meeting 2 of 93.34%, and meeting 3 of 93.78%. Of the three activity percentages, the percentage of relevant activities of students is 93.78% so that it can be said that the e-worksheet developed is very practical. The results of the e-worksheet effectiveness analysis were measured based on the score value of cognitive learning outcomes analyzed using the Wilcoxon test and classical completeness test and the value of critical thinking skills results analyzed using the t test and classical completeness test. The Wilcoxon test results on cognitive learning outcome scores obtained a significance value of 0.000 and a percentage of classical completeness test of 93.75%. The result of critical thinking skills value from t-test obtained a significance value of 0.000 and the percentage of classical completeness test was 96.88%. From both analysis results, the developed e-worksheet can be said to be effective. Based on the results of the analysis of validity, practicality, and effectiveness, it is found that the inquiry-flipped classroom e-worksheet to train critical thinking skills developed is suitable for use.